AN ANALYSIS OF THE EFFECT OF EARLY BAPTISM ON FAITHFULNESS IN THE CHURCH IN THE SEVENTH DAY ADVENTIST CHURCH MORIA HILL CHURCH BASED ON MARK 16:16 - Noti, Chiccof Stephenson Benerivo; Mangadar Simbolon (EZRA SCIENCE BULLETIN, 2024)
This study aims to analyze the effect of early baptism on church faithfulness in the Seventh-day Adventist Church, especially in the Moria Hill Congregation, with reference to Mark 16:16. The research method used is a qualitative method with a case study approach. Data were collected through in-depth interviews with congregation members who have experienced baptism, as well as analysis of Scripture texts and related literature. The results showed that baptism too early can negatively impact faithfulness in the church, as in some cases, individuals who are baptized too soon may not have fully understood their commitment to their faith. The implication of this finding is the importance of a careful approach in the baptismal process, by providing a deep understanding of faith commitment before one is baptized. This research is expected to contribute to the development of more effective and sustainable baptismal practices in the context of the Seventh-day Adventist church